Algorithm for the most surviving nodes selection based on adaptive forwarding control under the impact of network storm. (2018) - Wang, Zhi Chao; Shi, Hong Wei; Wei, Yan
In order to improve the survivability of wireless network nodes under the impact of network storm to improve the adaptive forwarding performance of network and control the nodes selection optimisation, an algorithm for the most surviving nodes selection based on adaptive forwarding control under the impact of network storm is proposed in this paper. In this algorithm, a node distribution model under the impact of network storm is constructed; the automatic regulation and control method is adopted for optimal localisation and deployment of target nodes; based on node location, an output link forwarding routing protocol is constructed for interference wave filtering and adaptive forwarding control of output package, so as to select the most surviving nodes and improve the survival rate of nodes. The simulation result shows that this method can realise 100% success rate of data forwarding, reduce the average transmission power by 5 kW than that before optimisation, and stabilise the transmission power. The calculation cost and time delay are 5-20 ms lower than that of other methods, which proves the high efficiency of this method.